Amplifiers the power of motivational leadership to inspire and influence - Church, Matt (Wiley, 2013)
Discover the secrets of motivational, inspirational, and transformational leadership. Great leaders do much more than just make decisions; they inspire those around them to excellence and form the vital link between strategy and execution. Amplifiers explains how great leaders use the art and practice of motivational leadership to light the path to success and inspire others to take that journey with them. Written by one of the most successful and well-known motivational speakers in Australia. Great leaders aren't born; they're made. For anyone who leads people, motivational leadership is the key to turning strategy into success. Read Amplifiers and boost your leadership skills to a higher level.